Biomethanation efficiency of para-grass in piggery wastewater in single stage and temperature phased anaerobic systems. (July 2018) - Saritpongteeraka, Kanyarat; Dechrugsa, Sumeth; Kantachote, Duangporn; Chen, Wen-Hsing; Chaiprapat, Sumate
Abstract: Effects of para-grass (PG) addition to pig manure (PM) digester were evaluated at organic loadings 0.10–3.76 gVS/L.d by different PG mixing ratios 0–8% in mesophilic single-stage (MS) and temperature-phased anaerobic digestion (TPAD, comprising T1 and M2 reactors) systems. Results showed equivalent methane production between MS and TPAD until 4%PG mix. Highest biogas yields obtained were 271.7 and 264.0 m 3 /tondry for MS and TPAD, respectively. Even with intense VFAs accumulation, the acidification yield in T1 was less than M2 because of continuous conversion of VFAs to CH4 . Only at higher loading (8%PG), reactor staging by temperature was justified for this co-digestion as TPAD exhibited a superior performance and lesser mass transfer impediment. Para-grass addition to PM digester shifted the domination of bacterial strains whereas achaea were steady. Higher microbial diversity and some evolving hydrolytic bacteria observed in T1 could contribute to greater system stability at high solid loading. An addition of small front-end thermophilic tank should be considered when expansion of the existing MS system is planned to process higher solid. Graphical abstract: fx1 Highlights: Para-grass is an abundant resource as co-substrate to piggery wastewater digestion. Highest CH4 yield obtained was 264–271 m 3 /ton dry matter at 4% grass mix, HRT 20d. Temperature-phased showed an advantage over one stage AD above 4% grass mix in feed. High microbial diversity in TPAD contributed to stable operation at high solid load. Adding small thermophilic tank to existing mesophilic system can be more economical.